2011
DOI: 10.1093/schbul/sbr142
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Functional, and Intertask Correlations of Measures Developed by the Cognitive Neuroscience Test Reliability and Clinical Applications for Schizophrenia Consortium

Abstract: The goal of the Cognitive Neuroscience Test Reliability and Clinical Applications for Schizophrenia (CNTRACS) Consortium was to develop measures of discrete cognitive processes, allowing for the interpretation of specific deficits that could be linked to specific neural systems. Here we report on the intertask, clinical, and functional correlates of the 4 tasks that were investigated in large groups of patients with schizophrenia (>100) and healthy controls (>73) at 5 sites across the United States. In both he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 38 publications
6
75
1
Order By: Relevance
“…Several studies have shown a linkage between visual perception and a range of adaptive functioning 16,17 and disorganized symptoms. 12 Although a recent large-sample study found no correlation between visual integration and community skills in SCZ, 18 this sample was relatively high functioning and had mild visual integration problems. Further, specific social cognitive processes may be more affected than broad measures of functional outcome in SCZ.…”
Section: Functional Correlates Of Visual Integrationmentioning
confidence: 65%
“…Several studies have shown a linkage between visual perception and a range of adaptive functioning 16,17 and disorganized symptoms. 12 Although a recent large-sample study found no correlation between visual integration and community skills in SCZ, 18 this sample was relatively high functioning and had mild visual integration problems. Further, specific social cognitive processes may be more affected than broad measures of functional outcome in SCZ.…”
Section: Functional Correlates Of Visual Integrationmentioning
confidence: 65%
“…21 However, in the current data set, we did not find significant correlations between CCE task performance and goal-maintenance performance (see ref. 36 ). As such, our findings suggest that the need for further research to establish the degree to which patients with schizophrenia show evidence of gain control abnormalities during visual perception independent of the effects of lapses in attention during the performance of this demanding task.…”
Section: Discussionmentioning
confidence: 99%
“…CNTRACS has addressed several of the challenges that the use of experimental paradigms developed from the cognitive neurosciences pose with respect to practical implementation in clinical research, including psychometric issues, use in multisite clinical studies, and relationship to functional outcomes. 64,65 The CNTRACS Consortium battery comprises tasks that assess visual processing, 66,67 episodic memory, 68 and goal maintenance, 69 and deficits among schizophrenia and schizoaffective patients using these measures have been observed. 70 Importantly, in a study examining the association between tasks on the CNTRACS and selected subtests from the MCCB, both common and unique deficits were detectible and shown to relate to functional impairments, albeit modestly.…”
Section: The Generalized Deficit and Evaluation Of Pharmacological Trmentioning
confidence: 99%